Postirradiation osteosarcoma of the occipital bone: A case report - Periasamy, Kannan; Karunanidhi, Gunaseelan; Vedasoundaram, Parthasarathy (Indian Journal of Case Reports, 2018)
Postirradiation osteosarcoma is an uncommon complication of radiation treatment for brain tumors. It is associated with a poor prognosis and survival is usually